1994
DOI: 10.7326/0003-4819-120-6-199403150-00004
|View full text |Cite
|
Sign up to set email alerts
|

Antiphospholipid Antibodies in Predicting Adverse Pregnancy Outcome: A Prospective Study

Abstract: Patients with elevated aPL levels at their initial prenatal visit had an increase in fetal loss but no increase in maternal pregnancy complications, low birth weight, or low Apgar scores. Immunoglobulin G anticardiolipin antibody was the only single test of aPL significantly associated with fetal loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
92
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 205 publications
(98 citation statements)
references
References 0 publications
5
92
0
1
Order By: Relevance
“…This timing is relevant, because the later in pregnancy that this sample is obtained, the higher the chance that early losses are not taken into account when the outcome in women with aPL and those without aPL is compared. Despite these shortcomings and differences, all studies found lower live-birth rates in aPL-positive women (range 62-84%) than in aPL-negative women (range 90-98%) (28,(40)(41)(42) (Table 2). An association between the presence of aPL and severe preeclampsia was found in 2 studies (28,42), but not in another study (40).…”
Section: Treatment Of Pregnancy In Women With Aplmentioning
confidence: 98%
See 4 more Smart Citations
“…This timing is relevant, because the later in pregnancy that this sample is obtained, the higher the chance that early losses are not taken into account when the outcome in women with aPL and those without aPL is compared. Despite these shortcomings and differences, all studies found lower live-birth rates in aPL-positive women (range 62-84%) than in aPL-negative women (range 90-98%) (28,(40)(41)(42) (Table 2). An association between the presence of aPL and severe preeclampsia was found in 2 studies (28,42), but not in another study (40).…”
Section: Treatment Of Pregnancy In Women With Aplmentioning
confidence: 98%
“…Despite these shortcomings and differences, all studies found lower live-birth rates in aPL-positive women (range 62-84%) than in aPL-negative women (range 90-98%) (28,(40)(41)(42) (Table 2). An association between the presence of aPL and severe preeclampsia was found in 2 studies (28,42), but not in another study (40). The Yasuda et al study (42) found a negative association and the Lynch et al study (40) found a positive association between aPL and neonatal birth weight.…”
Section: Treatment Of Pregnancy In Women With Aplmentioning
confidence: 98%
See 3 more Smart Citations